Development of fast breeder reactor technology in India. (November 2017) - Puthiyavinayagam, P.; Selvaraj, P.; Balasubramaniyan, V.; Raghupathy, S.; Velusamy, K.; Devan, K.; Nashine, B.K.; Padma Kumar, G.; Suresh kumar, K.V.; Varatharajan, S.; Mohanakrishnan, P.; Srinivasan, G.; et al.
Abstract: India is pursuing a three stage nuclear power program employing its natural uranium and Thorium reserves. FBRs form the second stage of the program linking the first phase with natural U and third phase with Th fuels. The saga of FBR technology development in India is presented in this paper. The valuable experience in design and operation of Fast Breeder Test Reactor (FBTR) is recounted briefly. The R&D for the techno-economic demonstration of Prototype Fast Breeder Reactor (PFBR) is explained including technology development for addressing manufacturing challenges and engineering full-scale qualification. Finally a brief projection is made on the developments for FBR600 with improved safety and economics as well as metal fuel technology for future experimental and power reactors to follow. Highlights: India's three stage nuclear program and Fast breeder reactor development in India. High performance of carbide fuel in FBTR. PFBR technology development and R&D. Engineering tests for full scale qualification. FBR 600 with improved economy and enhanced safety.